Hyperhomocysteinaemia is an independent risk factor for peripheral arterial disease in a Chinese Han population. (August 2017) - Rong, Dan; Liu, Jie; Jia, Xin; AL-Nafisee, Daniah; Jia, Senhao; Sun, Guoyi; Li, Yue; Lu, Weihang; Li, Haifeng; Zhang, Hongpeng; Ma, Xiaohui; Xiong, Jiang; et al.
Abstract: Background and aims: Hyperhomocysteineamia (HHcy) has long been suggested as a risk factor for atherosclerosis. However, the association between HHcy and peripheral arterial disease (PAD) is still controversial. There is a lack of research on this topic in the Chinese population. This study aims to provide further results. Methods: 240 PAD patients and 240 control subjects were evaluated for both serum total homocysteine levels and ankle brachial indexes (ABIs). Multivariable logistic regression models were used to estimate the association between HHcy and the risk of developing PAD. Interaction and stratified analyses were conducted according to age, sex, smoking status, drinking status, and histories of chronic disease. Results: The multivariate logistic regression analyses revealed that the risk of PAD was significantly associated with serum homocysteine levels. The interaction analysis showed no interactive role in the association between HHcy and PAD, indicating that homocysteine was associated with PAD independently of classical vascular risk factors. Conclusions: In conclusion, HHcy is an independent risk factor for PAD in the Chinese Han population. A prospective and randomized clinical trial of homocysteine lowering therapy in the Chinese population is needed to assess the causal nature of the relationship. Highlights: Participants with hyperhomocysteinaemia (HHcy) suffer a higher risk of peripheral arterial disease (PAD). HHcy is an independent risk factor for PAD in a Chinese Han population. This is the first case-control study to investigate the relationship between HHcy and PAD in Chinese mainland.